Coefficient inequalities for a subclass of bounded turning functions associated with a domain bounded by an epicycloid - Nithiyanandham, E. K.; Sruthakeerthi, B. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We consider a subclass of bounded turning functions BT_n-1,L associated with a domain bounded by an epicycloid with n-1 cusps. Our primary task is to examine some coefficient inequalities, as well as the second and third Hankel determinants for the newly defined class.